Pendampingan Tunagrahita Ringan melalui Permainan TASBIQI (Tangga Sosial Bernilai Qur’ani) di SLB Negeri Jenangan Ponorogo untuk Peningkatan Perilaku Sosial - Al Faritzi, Muhamad Redho Al Faritzi; Puspitasari, Niken Sylvia; Izzatullah, Hujjatul Islam Musthafa Abdurrahman Faiz; Pradana, Aditya Rizki (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
This community service activity aims to improve the social skills of students with mild intellectual disabilities through the innovative TASBIQI (Tangga Sosial Bernilai Qur'ani or Qur'anic Values Social Ladder) game, which integrates Qur'anic values such as honesty, cooperation, and responsibility into a fun learning process. The implementation method used a participatory and applicative approach with three main stages: socialisation, implementation, and evaluation. The community service was carried out for two weeks at the Jenangan Ponorogo State Special School, involving five students with mild intellectual disabilities and one accompanying teacher. Data was obtained through observation of social behaviour, simple pre-tests and post-tests, and joint reflection with teachers. The results of the activity showed a significant improvement in the students' social behaviour, particularly in honesty, cooperation, and communication, with an average score increase of around 35%. Teachers and students showed high enthusiasm, and the TASBIQI media was considered easy to adapt in the learning process. The novelty of this activity lies in the integration of Qur'anic values into interactive game media specifically designed for children with mild intellectual disabilities. The policy implications of this activity encourage schools and education stakeholders to adopt creative and contextual learning media in supporting inclusive education.